Revealing Trader's Sustainability in The Lok Baintan’s Floating Market - Sirajudin; Triyuwono, Iwan; Subekti, Imam (The International Journal of Accounting and Business Society, 2022)
Purpose — This paper revealed the trader’s sustainability in Lok Baintan’s floating market using an interpretive paradigm and the religionist phenomenological approach. Design/methodology/approach—A religionist phenomenology approach (which developed Husserl’s transcendental with a religionist paradigm) was used to conduct in-depth interviews and site observation. Some relevant literature was also used to sharpen the maps of findings.  Findings—The result states that Lok Baintan’s floating market is sustainable and supported by religious values. These values became a basic value for traders to survive in. Those traders believe that everything has its own fortune and has been arranged by God. This belief made them keep enlivening and trading along the river in Lok Baintan’s floating market. Practical implications — The belief that God has arranged all beings' fortunes has led traders to give up on the conditions of nature’s environment where they lived. This made them survive and enliven the Lok Baintan’s Floating Market. Originality/value — This paper argues that religious values and beliefs have influenced Banjarese (local people) to keep their simple lives lasting until now.  This is the key to sustainability in the Lok Baintan Floating Market.